Tension Pneumatocele due to Enterobacter gergoviae Pneumonia: A Case Report. (29th September 2012) - Kesieme, Emeka B.; Kesieme, Chinenye N.; Akpede, George O.; Okonta, Kelechi E.; Dongo, Andrew E.; Gbolagade, Adewuyi M.; Eluehike, Sylvester U.
Abstract : Pneumatocele formation is a known complication of pneumonia. Very rarely, they may increase markedly in size, causing cardiorespiratory compromise. Many organisms have been implicated in the pathogenesis of this disease; however, this is the first report of tension pneumatocele resulting from Enterobacter gergoviae pneumonia. We report a case of a 3-month-old Nigerian male child who developed two massive tension pneumatoceles while on treatment for postpneumonic empyema due to Enterobacter gergoviae pneumonia. Tube thoracostomy directed into both pneumatocele resulted in complete resolution and recovery. Enterobacter gergoviae is a relevant human pathogen, capable of causing complicated pneumonia with fatal outcome if not properly managed. In developing countries where state-of the-art radiological facilities and expertise for prompt thoracic intervention are lacking, there is still room for nonoperative management of tension pneumatocele especially in very ill children.